2017
DOI: 10.1038/ncomms14819
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde transport of TrkB-containing autophagosomes via the adaptor AP-2 mediates neuronal complexity and prevents neurodegeneration

Abstract: Autophagosomes primarily mediate turnover of cytoplasmic proteins or organelles to provide nutrients and eliminate damaged proteins. In neurons, autophagosomes form in distal axons and are trafficked retrogradely to fuse with lysosomes in the soma. Although defective neuronal autophagy is associated with neurodegeneration, the function of neuronal autophagosomes remains incompletely understood. We show that in neurons, autophagosomes promote neuronal complexity and prevent neurodegeneration in vivo via retrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
195
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 70 publications
6
195
1
Order By: Relevance
“…Currently, there is no known cellular mechanism directly linking KIM‐1 and BDNF . Interestingly, recent studies have shown that both proteins are involved in autophagy, an important process for cell survival …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no known cellular mechanism directly linking KIM‐1 and BDNF . Interestingly, recent studies have shown that both proteins are involved in autophagy, an important process for cell survival …”
Section: Discussionmentioning
confidence: 99%
“…Synj1 appears critical in this process and regulates, together with a handful of other proteins such as Bassoon and EndoA, the formation of autophagosomes at synapses (Fig B). EndoA and Synj1 also regulate synaptic vesicle endocytosis, but defects in endocytosis and autophagy are not mutually exclusive and connections between the two processes have been described (Ravikumar et al , ; Kononenko et al , ).…”
Section: Synaptic Autophagymentioning
confidence: 99%
“…Recent work from the team of Volker Haucke using cortical and hippocampal neurons has shown that AP2μ interacts with LC3b and regulates the retrograde transport and maturation of autophagosomes via a mechanism independent of its established role as a clathrin adaptor. pTrkB is found in AP2μ‐ and LC3b‐positive organelles and a knockout mouse of AP2μ exhibited a decrease in both the retrograde transport of TrkB and dendritic complexity .…”
Section: A New Organelle or A Master Of Disguise?mentioning
confidence: 98%